The Modelling Concept of Volume and Duration of Parking for Various Types of Landuse in Surabaya - Gde Kartika, Anak Agung; Mochtar, Indrasurya B.; Widyastuti, Hera (Institut Teknologi Sepuluh Nopember, 2017)
Both parking fee and parking tax are the potential income for most local authorities in Indonesia since they are considered as the parts of of local authority’s revenue (Pendapatan Asli Daerah, PAD). However, currently many local authorities including that in Surabaya has a problem in determining target as well as the achievement of annual parking revenue. This situation takes place due to the lack of reliable method to estimate the parking revenue including both parking fee and parking tax either on-street parking nor off-street parking. Meanwhile, there are growing investments of public and private facilities in many capital cities of both regency and provincy including apartments, hotels, malls, campus, hospitals, convention buildings, terminals, offices, restaurants and mixed uses in which many parking spaces will be provided to support their activities later on. The providing of new parking spaces will therefore potentially contribute to the local authorities’s revenue as the consequences. Main variable to contribute the parking revenue are the number of parked vehicle as well as the parking duration (when progressive tariff is applied). The concept of both number of parked vehicle and parking durations for several landuses will be introduced in this paper so that they can be elaborated more in depth as a mathematical model. Furthermore they can be used as references for estimating the anual parking revenue of local authotities as the part of local authorities revenue (PAD). Moreover, these models will be useful for parking facilities investors to analyse the their financial investment.